EVALUATION OF FREE RADICAL SCAVENGING ACTIVITY OF MIMOSA PUDICA THORNS - R, Lakshmibai; D, Amirtham (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Mimosa pudica is a traditional medicinal plant. The natural antioxidant compounds from plants mop up the free radicals causing cell damage and maintain the biological systems. The aim of the present study is to evaluate the free radical scavenging potential of the ethanolic and aqueous thorn extracts of M. pudica. Methods: The ethanolic and aqueous thorn extracts of M. pudica were analyzed for the phytochemicals and for free radical scavenging activity by 1, 1 diphenyl 1-2-picric hydrazine (DPPH), 2, 2’-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), and nitric oxide free radical scavenging method. Results: Flavonoids, saponins, glycosides, alkaloids, terpenoids, and coumarins were the phytoconstituents revealed in ethanolic and aqueous thorn extracts of M. pudica. At 250 Î¼g/mL concentrations, aqueous thorn extracts of M. pudica exhibited 73.41% radical scavenging activity by DPPH method and 26.10% inhibition by nitric oxide free radical scavenging method. However, the ethanolic extracts of M. pudica thorns exhibited 73.35% inhibition by ABTS free radical scavenging method at 250 Î¼g/mL concentrations. Conclusion: The results obtained suggest that the plant extracts from M. pudica could serve as a potential source of antioxidant in slowing down the process of aging and age-related or oxidative stress-related degenerative diseases. Moreover, the isolation of bioactive principle responsible for the antioxidant activity and formulation of novel therapeutic agents can be further studied.